Bricks matter : the role of supply chains in building market-driven differentiation - Cecere, Lora M.; Chase, Charles W. (Hoboken, New Jersey : Wiley, 2012)
Get proven guidance to build a market-driven supply chain management system Supply chain management processes have gradually shifted from a supply-driven focus to a demand-driven one in order to better synchronize demand and supply signals. Bricks Matter shows you how you can identify market risks and opportunities and translate these into winning tactics. Business cases highlight how business leaders are winning through market-driven approaches. Helps you understand how to apply the emerging world of predictive analytics for the better management of value networks>
Foreword -- Preface -- Bricks matter -- Building value networks -- The new world of demand management : demand sensing, shaping, and translation -- The new world of supply management -- About the authors -- Index.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business logistics; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business logistics; Electronic books; Electronic books